Financial services in the development and execution of infrastructures for their integration into value chains - Chavarry Vallejos, Carlos Magno; Panana Holgado, Elizabet Clotilde; Solorzano Poma, Javier Eloy; Minaya Huerta, David; Javier Cabana, Luis Teodisio; Silva Lindo, Marco Antonio; Coral Jamanca, Julio Cesar (LACCEI, 2024)
The research entitled financial services in the development and execution of infrastructure for its integration into value chains, aims to promote inclusive and sustainable industrialization, contribute to industry, employment, gross domestic product and the access of small industries to financial development and integration into value chains and markets. Based on statistical information, an improvement plan was established associated with financial services in the development and execution of infrastructure. The research method is deductive, qualitative, applied orientation and descriptive, correlational and explanatory. The design is non-experimental, cross-sectional and prospective. For the present study, a population (N) of 297 was considered, with the observation unit being consulting companies and contractors, and the analysis unit being professionals dedicated to the management, direction and design of infrastructure projects. A sample (n) of 169 was obtained. The technique for obtaining the information was the personal interview. As a data collection instrument, a semi-structured questionnaire was developed consisting of closed questions with polytomic values. The Likert scale was used with queries ranging from positive (very frequently) to negative (never). The study determined that 6% of them frequently develop financial services focused on the Sustainable Development Goals (SDGs). The instrument has a good internal reliability, because a Cronbach’s alpha coefficient = 0.858 was obtained. The average correlation was 0.525, which is a considerable positive correlation.